An analysis of micro enterprise development factors in dealing business competition in Medan city - Raihanah Daulay; Siti Mujiatun (Proceedings of AICS - Social Sciences, 2017)
Micro-enterprise as a business that absorbs the most labor and occupy the third position of the wheels of the economy. In its development, micro business still experience obstacles, making it difficult to compete especially when dealing with franchise business. Various obstacles are faced by micro business actors will be solved by solving from the factors of business development. This study aims to apply the model of micro business development in Medan City. The model is expected to assist micro businesses to be able to compete and thrive, with fostering the businessmen through the program and entrepreneurship skills. The research method used is Action Research. The study was conducted in three stages. The first stage was the survey mapping the conditions and capabilities of micro-enterprises. The second stage was analyzing the factors of micro business development and socialization. The third stage was implementation of micro enterprise development factor and to see the change of micro business.